Swedish Crime Fiction in the Soviet Union. Publication and Paratextual Framing - Podlevskikh Carlström Malin (Svenska Litteratursällskapet, 2025)
This article investigates the publication and paratextual framing of Swedish crime fiction in the Soviet Union. Based on an analysis of the written peritexts of 21 editions, conclusions are drawn regarding: 1) the representation of the genre of crime fiction, and in particular Swedish crime fiction; 2) the representation of Swedish crime fiction authors; 3) the representation of the source culture of Sweden; 4) ideological aspects of the paratextual framing. A premise for the analysis is that in a literary system governed by strict censorship, the peritext becomes a tool used by the censorship apparatus, and industry-created peritexts are often ideologically motivated. The analysis reveals that Swedish crime fiction and Swedish crime fiction authors are clearly distinguished from the general Anglo-American crime fiction genre. Swedish crime fiction is described as being written by authors whose main purpose is not to entertain the reader, but rather to reveal the truth about social injustice and capitalist society. Secondly, positive representations of Sweden are ironically corrupted and used in combination with details
from the storyline of crime fiction novels in order to show that all positive representations of Sweden and Western society are false. Thirdly, the paratext creators try to convince the reader that gruesome images of Sweden from crime fiction novels are true representations of everyday life in Sweden. To conclude, it is clear that state censorship was involved in both the selection and the paratextual framing of Swedish crime fiction in the Soviet Union. Furthermore, it is reasonable to assume that the real purpose behind the publication of Swedish crime fiction was not related to literature as such. Instead, these novels were deliberately selected for publication in the Soviet Union for the purpose of corrupting the image of Sweden and creating a representation that better suited the ideology of the State.